A CHILD WITH X LINKED INHERITED INTELLECTUAL DISABILITY - V Jogi, Samadhara; S Kumar, Vikram; Kamble, Niranjan; Rajatadri Rangaswamy, Darshan (Journal of Chitwan Medical College, 2024)
X-linked intellectual disability, also known as X-linked mental retardation, is a neurodevelopmental disorder caused by a gene defect on the X chromosome. While more than 100 genes have been linked to X linked intellectual disability, the genetic aetiology of intellectual disability remains unknown in approximately half of the cases. Intellectual disability often co-occurs with other conditions like epilepsy and autism spectrum disorder. X-linked 98-related intellectual disability syndrome is a rare neurodevelopmental disorder due to Neurite extension and migration factor gene mutation characterised by global developmental delay, intellectual disability, and language delay, with or without autistic features. Distinctive characteristics include coarse facial features, a protruding tongue, and behavioural abnormalities such as excessive tantrums and intrusiveness. The case study presented involves a child with a stop-gain variant in the Neurite extension and migration factor gene presenting with autism spectrum disorder, specific learning disability and behavioural abnormalities with interesting phenotypic features.